Field Guide for the Identification of Damage on Woody Sentinel Plants - Roques, Alain (CABI, 2017)
This guide is intended as an aid for managers of sentinel plantings, botanical gardens or arboreta, as well as phytosanitary inspectors, who may have knowledge of common pests and diseases of woody plants, but may not know the likely cause of damage that they have not encountered before. It aims to provide a tentative identification of relatively broad groups of organisms and not definitive identification of the causal agents. Hence, the pictures in this guide need to be regarded as typical examples of the described symptoms. There are chapters that explain how to use the guide, followed by keys (for different organs of conifer and broadleaf species) to guide the user to the relevant sections of the book, based on the questions entomologists and pathologists ask themselves when looking at a damaged or diseased tree in a fashion similar to how a doctor interrogates a patient to arrive at a diagnosis. The largest part of the book is devoted to the description and illustration of damage types and typical causes of the observed damage. The last chapters provide instructions for taking and preserving samples for further identification by an expert, notification of relevant authorities, and a glossary.